(untitled) (Research, Society and Development, 2022)
Hematological tests are essential in investigating the etiology and chronicity of diseases, in addition to helping in research. However, reference values for blood count and biochemical parameters of wild cats are scarce, restricting treatment and prevention measures, aggravating the risks of extinction of this species. This study aimed to study the blood count and biochemical parameters of healthy wild cats kept in captivity in a conservation center in Ribeirão Preto (SP). Blood samples were collected from six wild cats, including four Puma concolor, one Panthera onca, and one Panthera leo. As for the blood count, the values ​​of red blood cells, hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, platelets, total leukocytes, myelocytes, metamyelocytes, rods, segmented, lymphocytes, monocytes, eosinophils, and basophils were analyzed. Regarding biochemical parameters, the values ​​of aspartate aminotransferase, alanine aminotransferase, gamma-glutamyl transferase, alkaline phosphatase, creatine kinase, urea, creatinine, blood urea nitrogen (BUN), BUN/creatinine ratio, total protein, albumin, globulin, fibrinogen, total cholesterol, triglycerides, serum iron, calcium, phosphorus, and amylase were studied. In addition to the literature, the blood count and biochemical values found in this study indicate that there may be variations in hematological parameters as a function of the sex of the animal and between captive and free-living populations. Furthermore, in this study, some hematological parameters of wild cats differed from those references for domestic cats.